2019
DOI: 10.1371/journal.pone.0224737
|View full text |Cite
|
Sign up to set email alerts
|

Non-intubated anesthesia in patients undergoing video-assisted thoracoscopic surgery: A systematic review and meta-analysis

Abstract: IntroductionNon-intubated anesthesia (NIA) has been proposed for video-assisted thoracoscopic surgery (VATS), although how the benefit-to-risk of NIA compares to that of intubated general anesthesia (IGA) for certain types of patients remains unclear. Therefore, the aim of the present meta-analysis was to understand whether NIA or IGA may be more beneficial for patients undergoing VATS.MethodsA systematic search of Cochrane Library, Pubmed and Embase databases from 1968 to April 2019 was performed using predef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 57 publications
0
23
0
1
Order By: Relevance
“…NIVATS is a safe and feasible alternative procedure and improves postoperative rehabilitation by reducing postoperative complications, hospital stay, and attenuating stress and inflammatory responses [ 10 , 13 , 14 ]. However, few specific analyses of risk factors for NIVATS have been conducted even though the procedure has been used in a large number of patients [ 27 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…NIVATS is a safe and feasible alternative procedure and improves postoperative rehabilitation by reducing postoperative complications, hospital stay, and attenuating stress and inflammatory responses [ 10 , 13 , 14 ]. However, few specific analyses of risk factors for NIVATS have been conducted even though the procedure has been used in a large number of patients [ 27 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence supporting non-intubated VATS as the preferred approach for lung surgery is still limited. Previous meta-analyses reported that non-intubated procedure attenuated the in ammatory response and stress, followed by fewer postoperative complications as compared with the intubated VATS [15,16]. Moreover, the indications for VATS could be extended by this less-invasive procedure.…”
Section: Discussionmentioning
confidence: 98%
“…The data from this metaanalysis support this. Previous meta-analyses showed that patients undergoing non-intubated thoracoscopic surgery had shorter hospital stays and postoperative fasting (43), less postoperative inflammation, and better immune function recovery (44). However, most of the included studies were retrospective studies, and the selection and reporting bias may have affected the study results.…”
Section: Discussionmentioning
confidence: 99%